2020
DOI: 10.1103/physreva.102.012425
|View full text |Cite
|
Sign up to set email alerts
|

Quantum blackjack: Advantages offered by quantum strategies in communication-limited games

Abstract: We examine the advantages that quantum strategies afford in communication-limited games. Inspired by the card game blackjack, we focus on cooperative, two-party sequential games in which a single classical bit of communication is allowed from the player who moves first to the player who moves second. Within this setting, we explore the usage of quantum entanglement between the players and find analytic and numerical conditions for quantum advantage over classical strategies. Using these conditions, we study a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Interestingly, in contrast to most quantum information games (see e.g. references [35,51] for exceptions) this communication scenario admits an elegant interpretation in terms of the real-life colloquial game of Battleship, as detailed in reference [52] (where the game is also independently introduced). The algebraically maximal witness value is W = 36, which corresponds to earning one point for each pair (x, y).…”
Section: Can Qutrits Outperform Qubits Assisted By Qubit-entanglement?mentioning
confidence: 99%
“…Interestingly, in contrast to most quantum information games (see e.g. references [35,51] for exceptions) this communication scenario admits an elegant interpretation in terms of the real-life colloquial game of Battleship, as detailed in reference [52] (where the game is also independently introduced). The algebraically maximal witness value is W = 36, which corresponds to earning one point for each pair (x, y).…”
Section: Can Qutrits Outperform Qubits Assisted By Qubit-entanglement?mentioning
confidence: 99%
“…In section I, we introduced quantum effects in game theory [2][3][4][5] and the application to gambling [6][7][8][9][10][11][12][13][14][15][16]. We also mentioned what will happen when playing blackjack on a quantum computer.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that this can be improved using quantum error mitigation techniques. In blackjack, it was shown that the players can have advantages compared to the dealer, using entangled bit communication between two players by [16]. As you can see in these studies, not a few games have been examined by using quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…In [17] the optimal strategy for Blackjack is discussed, where a mathematical expression is derived, providing a general solution to the player's problem of drawing additional cards, with a given hand, or not. The game is also used in [18] as a baseline for examining the advantages that quantum strategies allow in communicationlimited games. Regarding Baccarat, it has been shown in [19] that, differently from Blackjack, the "card counting" technique does not provide significant favorable strategies, both for the Trente-et-Quarante and "Nevada" variants.…”
Section: A Related Workmentioning
confidence: 99%